Genome-Wide Association Study on Root Traits Under Different Growing Environments in Wheat (Triticum aestivum L.) - Xu, Fengdan; Chen, Shulin; Yang, Xiwen; Zhou, Sumei; Wang, Junsen; Zhang, Ziliang; Huang, Yuan; Song, Miao; Zhang, Jun; Zhan, Kehui; He, Dexian (Frontiers in Genetics, 2021)
Plant roots are critical for water and nutrient acquisition, environmental adaptation, and yield formation. Herein, 196 wheat accessions from the Huang-Huai Wheat Region of China were collected to investigate six root traits at seedling stage under three growing environments (indoor hydroponic culture (IHC), outdoor hydroponic culture (OHC), and outdoor pot culture (OPC)) and the root dry weight (RDW) under OPC at four growth stages and four yield traits under four environments. Additionally, a genome-wide association study was performed with a Wheat 660K SNP Array. The results showed that the root traits varied most under OPC, followed by those under both OHC and IHC, and root elongation under hydroponic culture was faster than that under pot culture. Root traits under OHC might help predict those under OPC. Moreover, root traits were significantly negatively correlated with grain yield (GY) and grains per spike (GPS), positively correlated with the thousand-kernel weight (TKW), and weakly correlated with the number of spikes per area (SPA). Twelve stable chromosomal regions associated with the root traits were detected on chromosomes 1D, 2A, 4A, 4B, 5B, 6D, and Un. Among them, a stable chromosomal interval from 737.85 to 742.00 Mb on chromosome 4A, which regulates total root length (TRL), was identified under three growing environments. Linkage Disequilibrium (LD) blocks were used to identify 27 genes related to root development. Three genes including TraesCS4A02G484200, TraesCS4A02G484800, TraesCS4A02G493800, and TraesCS4A02G493900, are involved in cell elongation and differentiation and were highly expressed in root tissues. Another vital co-localization interval on chromosome 5B (397.72-410.88 Mb) was associated with not only RDW under OHC and OPC but also TKW.